Human nature and nature of power - IBRAGIMOVA, Z.Z.; RAISOVICH, M.S. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The resource to the phenomena of human nature and power nature is dictated in a way by the belief that there is much more than only correlation and proportionality between them: these are two forms of sociality. Power still carries out a crucial function in society: it helps a person orient himself in life and defend off all metamorphoses and distortions of power. The ontological status of two phenomena is possible when true sociality is achieved, that is what we call humanity. The main methods used in writing this article are the method of historical and logical unity and the method of comparative analysis. RESUMEN El recurso a los fenómenos de la naturaleza humana está dictado en cierto modo por la creencia de que hay mucho más que solo correlación y proporcionalidad entre ellos: estas son dos formas de socialidad. El poder aún cumple una función crucial en la sociedad: ayuda a una persona a orientarse en la vida y a defenderse de todas las metamorfosis. El estado ontológico de dos fenómenos es posible cuando se logra la verdadera socialidad, lo que llamamos humanidad. Los principales métodos utilizados para escribir el artículo son el método histórico, la unidad lógica y el método de análisis comparativo.